Population pharmacokinetic study of isepamicin with intensive care unit patients. - Tod, M (1996)
The pharmacokinetics (PK) of isepamicin, a new aminoglycoside, were studied in 85 intensive care unit (ICU) patients and were compared with those observed in 10 healthy volunteers. A parametric method based on a nonlinear mixed-effect model was used to assess population PK. Isepamicin was given intravenously over 0.5 h at dosages of 15 mg/kg once daily or 7.5 mg/kg twice daily. The data were fitted to a bicompartmental open model. Compared with healthy volunteers, the mean values of the PK parameters were profoundly modified in ICU patients: elimination clearance was reduced by 48%, the volume of distribution in the central compartment (Vc) was increased by 50%, the peripheral volume of distribution was 70% higher, the distribution clearance was 146% lower, and the elimination half-life was ca. 3.4 times higher. The interindividual variability in PK parameters was about 50% in ICU patients. Five covariates (body weight [BW], simplified acute physiology score [SAPS], temperature, serum creatinine level, and creatinine clearance [CLCR]) were tentatively correlated with PK parameters by multivariate linear regression analysis with stepwise addition and deletion. The variability of isepamicin clearance was explained by three covariates (BW, SAPS, and CLCR), that of Vc was explained by BW and SAPS, and that of the elimination half-life was explained by CLCR and SAPS. Simulation of the concentration-versus-time profile for 500 individuals showed that the mean peak (0.75 h) concentration was 18% lower in ICU patients than in healthy volunteers and that the range in ICU patients was very broad (28.4 to 95.4 mg/liter). Therefore, monitoring of the isepamicin concentration is in ICU patients is mandatory.